2011
DOI: 10.1186/1743-422x-8-213
|View full text |Cite
|
Sign up to set email alerts
|

Human-derived IgG level as an indicator for EBV-associated lymphoma model in Hu-PBL/SCID chimeras

Abstract: BackgroundEpstein-Barr virus (EBV) has a close association with various types of human lymphomas. Animal models are essential to elucidate the pathogenesis of human EBV-associated lymphomas. The aim of the present study is to evaluate the association between human IgG concentration and EBV-associated lymphoma development in huPBL/SCID mice.MethodsHuman peripheral blood lymphocytes (hu-PBL) from EBV-seropositive donors were inoculated intraperitoneally into SCID mouse. Immunohistochemical staining was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…HMs can also be generated by the direct injection of human peripheral blood. In one early cancer study, Tang, et al injected purified human blood lymphocytes from donors infected with Epstein-Barr virus into SCID mice and monitored these animals for indications of human B cell lymphoma (20). In other cases, mice are classified as humanized after the implantation of human stromal tissue together with the tumor tissue.…”
Section: State Of the Art In Cancer Researchmentioning
confidence: 99%
“…HMs can also be generated by the direct injection of human peripheral blood. In one early cancer study, Tang, et al injected purified human blood lymphocytes from donors infected with Epstein-Barr virus into SCID mice and monitored these animals for indications of human B cell lymphoma (20). In other cases, mice are classified as humanized after the implantation of human stromal tissue together with the tumor tissue.…”
Section: State Of the Art In Cancer Researchmentioning
confidence: 99%
“…This indicated that the induced tumors originated from human cells rather than mouse cells. In our previous study, the concentration of human IgG in the sera of hu‐PBL/SCID chimeric mice was monitored continuously, and the results showed that the levels of IgG gradually increased with the growth of the induced tumors [Tang et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have demonstrated that EBV can transform and even immortalize normal human peripheral lymphocytes [10]. Our group was among the first to transplant EBV-infected human peripheral lymphocytes (hu-PBL) from healthy blood donors into severe combined immunodeficiency (SCID) mice to induce the generation of human-derived B cell lymphomas [11,12]. However, the cellular and molecular mechanisms of malignant transformation of normal lymphocytes and tumor formation induced by EB virus remain unclear.…”
Section: Introductionmentioning
confidence: 99%